Bureaucratic Reform Within The Indonesian National Army; An Institutional Perspective - Wijanarko, Trias; Saputro, Guntur Eko; Andreas N, Djoko (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2025)
Bureaucracy reform within the Indonesian National Army (TNI) is a strategic step to improve good and clean governance in the face of the dynamics and demands of global environmental changes. Despite various efforts that have been made, the implementation of bureaucracy reform in the TNI still faces challenges related to inefficiency, internal resistance, and a bureaucratic culture that holds a strong hierarchy. The main problem raised in this study is how bureaucracy reform can encourage transparency, accountability, and increased efficiency in TNI institutions. This study aims to analyse the effectiveness of bureaucracy reform in realizing good and clean governance within TNI by using the institutional theory. The method used is a literature review by reviewing various policy documents, previous research reports, and relevant publications to understand the implementation of bureaucracy reform within the TNI. Institutional theory emphasizes three essential pillars, namely the regulatory pillar, normative pillar, and cultural cognitive pillar, where these three factors are the framework of analysis in this study. The results of the study show that these three factors significantly affect the efforts to change the institution carried out through bureaucracy reform. Increased transparency and accountability have been achieved in some parts of the Organization, but to realize good and clean governance as a whole, commitment and consistency are still needed in the implementation of sustainable bureaucracy reform.